Development of the modern assortment concept of trade enterprises - T.O. Biliak (Економіка, управління та адміністрування)
The article examines the process of formation and development of the modern assortment concept of trade enterprises. It was determined that the study of scientific-methodical and applied aspects of the development of the modern assortment concept of trade enterprises will allow Ukrainian companies to more rationally adapt to the conditions of an unstable external environment and achieve the set goals in their own trade system. It is justified that the assortment concept of a trading enterprise is a strategic approach to managing the assortment of goods or services, which is aimed at achieving an optimal balance between the needs of consumers and the ability of the enterprise to satisfy these needs. The goal of forming an assortment concept of a trade enterprise is summarized, which consists in achieving an optimal and effective distribution of goods or services within the company’s assortment in order to satisfy consumer needs and achieve strategic business goals. The main tasks of the assortment concept of trade enterprises are defined, which include: studying the needs and requirements of the target audience; optimization of product range; ensuring the dynamism of the product range; forming the effectiveness of the product range. It has been established that the formation of a rational assortment concept of a trade enterprise is based on several key principles aimed at creating an optimal and effective assortment of goods or services, among which the following are highlighted: customer orientation, dynamism, uniqueness, efficiency. It is substantiated that the transformation of the modern assortment concept is an important factor in the success of trade enterprises in the latest changing conditions. It is structured by the main stages of the process of development and implementation of the assortment concept of the trade enterprise. Specific areas of using digital technologies for the formation of an effective assortment of products within the framework of the developed assortment concept are presented.